Light and CO(2) Response of Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase Activation in Arabidopsis Leaves - Salvucci, Michael E. (1986)
The requirements for activation of ribulose 1,5-bisphosphate carboxylase/oxygenase (rubisco) were investigated in leaves of Arabidopsis wild-type and a mutant incapable of light activating rubisco in vivo. Upon illumination with saturating light intensities, the activation state of rubisco increased 2-fold in the wild-type and decreased in the mutant. Activation of fructose 1,6-bisphosphate phosphatase was unaffected by the mutation. Under low light, rubisco deactivated in both the wild-type and the mutant. Deactivation of rubisco in the mutant under high and low light led to the accumulation of high concentrations of ribulose 1,5-bisphosphate. Inhibiting photosynthesis with methyl viologen prevented ribulose 1,5-bisphosphate accumulation but was ineffective in restoring rubisco activation to the mutant. Net photosynthesis and the rubisco activation level were closely correlated and saturated at a lower light intensity in the mutant than in wild-type. At CO(2) concentrations between 100 and 2000 microliters per liter, the activation state was a function of the CO(2) concentration in the dark but was independent of CO(2) concentration in the light. High CO(2) concentration (1%) suppressed activation in the wild-type and deactivation in the mutant. These results support the concept that rubisco activation in vivo is not a spontaneous process but is catalyzed by a specific protein. The absence of this protein, rubisco activase, is responsible for the altered characteristics of rubisco activation in the mutant.